Predict organizational citizenship behavior of the staff based on the factors of the job satisfaction - Khaidan Hatamı; Mohhammad Reza Esmaeılı; Sayed Hamid Sajadı (Türk Spor ve Egzersiz Dergisi)
The aim of the present study was to predict organizational citizenship behavior of the staff of the Ministry of Sport and Youth in the west part of the country based on the factors of the Job Satisfaction. The research methodology employed was applied and practical. The population of the research consisted of all employees in the departments of the ministry of Sport and Youth in the west part of the country in the year 1394 including 266 personnel among whom 164ones were selected as research samples. In order to collect information, for collecting data on Job Satisfaction variable, the Standard Job Satisfaction questionnaire of Minnesota was used, and to collect data on the organizational citizenship behavior variable, the organizational citizenship behavior questionnaire of Podsakoff et al. was used. For data analysis, Kolmogorov-Smirnov inferential statistics was used to determine the normal distribution of data and the analysis of variance. For all Statistical Activities, SPSS statistical software version 22 with the confidence level 95% was used. The research results showed that there was a significant relationship between Job Satisfaction and its components and organizational citizenship behavior. And the examination of the predictor variables showed that organizational climate can significantly explain the citizenship behavior variance.